2021
DOI: 10.1002/dac.4914
|View full text |Cite
|
Sign up to set email alerts
|

Analytical outage and coverage performance analysis of cell‐free massive MIMO system based on radio stripe

Abstract: Summary Cell‐free mMIMO (massive multiple input multiple output) is slated to be beyond 5G (B5G) wireless technology, given the attractive features it offers, higher spectral efficiency, higher‐energy efficiency, and superior spatial diversity. However, large numbers of long cables between each access point (AP) and central processing unit (CPU) (front haul requirements) mar its practical adoption. Radio stripe is one such architecture of cell‐free mMIMO suitable for practical deployment. In this work, we deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The authors compared the macro-diversity and signal spatial diversity performance of traditional mMIMO with different D-mMIMO setups, such as RS, and found that D-mIMO can provide higher average channel gains. In [122], the outage and coverage probabilities in the UL and DL of an RS network are analyzed. The study demonstrated good system performance when the number of APs exceeded the number of UEs.…”
Section: Developments On Radio Stripe Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors compared the macro-diversity and signal spatial diversity performance of traditional mMIMO with different D-mMIMO setups, such as RS, and found that D-mIMO can provide higher average channel gains. In [122], the outage and coverage probabilities in the UL and DL of an RS network are analyzed. The study demonstrated good system performance when the number of APs exceeded the number of UEs.…”
Section: Developments On Radio Stripe Technologymentioning
confidence: 99%
“…Uplink (UL) NLMMSE-based [115] OSLP-based [116] RZF-based [119] Quasi-LMMSE-based [120] Clustered-based [123] Cluster-MMSE-based [137] MRT-based [118] Spatial Diversity Performance [121] Exploration [126] Integration [127] Outage Probabilities [122] LDPC codification [136] Comparison with CF [16] Comparison with LIS [138] Low-pass [124,125] Joint Positioning and synchronization with ML [133] APS to improve PE [135,139] SO power optimization [128] BO power optimization [129] BO APS to improve SE/LB [131] MO power optimization [130]…”
Section: Resource Allocation (Ra)mentioning
confidence: 99%
“…In this context, considerable literature has been investigated the performance of CF massive MIMO for the sake of optimizing the EE, SE, CP, throughput, and achievable rate, by exploiting the benefits of spatial multiplexing macrodiversity, channel hardening, and favorable propagation conditions. [13][14][15][16][17][23][24][25] For instance, in Ngo et al, 16 the authors have investigated the performance of CF massive MIMO networks by mainly considering the effects of imperfect (CSI), pilot assignment, and power control. This study has proven that the CF massive MIMO enhances the system performances compared to the SC massive MIMO system in terms of throughput.…”
Section: Related Workmentioning
confidence: 99%
“…These APs are connected to a central processing unit (CPU) by backhaul links. Recently, the CF massive MIMO approach has caught the attention of the research community as it reaps all massive MIMO performances (e.g., reliability, macro‐diversity, channel hardening, and favorable propagation) and due to its architecture and performances in terms of throughput, EE, SE, and CP 14,15 . CF massive MIMO concept has also covered the weaknesses of SC systems in terms of excessive handover.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation